Police officer knowledge of and attitudes to opioid overdose and naloxone administration: an evaluation of police training in Scotland - Hillen, Peter (Policing and society, 2025)
In the context of escalating drug-related deaths, during 2021 Police Scotland implemented a pilot project incorporating naloxone training to test the carriage and administration of naloxone by officers. The current paper presents data from the evaluation of this pilot exploring knowledge of, and attitudes to, opioid overdose and naloxone administration. Police officers completed a three-stage survey which included a modified Opioid Overdose Knowledge Scale (OOKS) and Opioid Overdose Attitudes Scales (OOAS). In total, 167 police officers completed the survey before taking part in the training; 144 completed a post-training survey; and 88 completed a follow-up survey. Training improved officers’ knowledge and attitudes about drug overdose and naloxone administration. The OOKS mean total score improved from 35.8 pre-training to 37.6 at follow-up (‘small-medium’ effect size; Cohen’s d = 0.42). The OOAS mean total score improved from 87.8 pre-training to 100.7 at follow-up (‘large’ effect size; Cohen’s d = 1.05). Training was also reported to facilitate the acceptability of naloxone administration as part of a police officer’s role. However, over a third of officers questioned the relevance of the training to their role. There was evidence that some officers held stigmatising attitudes towards people who use drugs (PWUD). Future training should address officers’ knowledge of problem drug use and stigmatising attitudes towards PWUD, and train and support officers to respond to the emergent public health role of policing. The findings of this evaluation informed the decision of the Chief Constable of Police Scotland to mandate that all Police Scotland Officers routinely carry naloxone from August 2022.